The influence of Continuous Quality Improvement on healthcare quality: A mixed-methods study from Zimbabwe. (April 2022) - Gage, Anna D.; Gotsadze, Tamar; Seid, Endris; Mutasa, Ronald; Friedman, Jed
Abstract: In an effort to improve the poor quality of maternal, newborn, and child health services, the Zimbabwe Ministry of Health and Child Care implemented a Continuous Quality Improvement (CQI) pilot in 2016. Health workers and district managers were trained and supported to implement cycles of quality target setting, developing and implementing action plans, and tracking outcomes. The pilot was implemented in district hospitals and primary health centers in five districts as an arm of the performance-based health financing (PBF) program. This study uses mixed methods to estimate the effect of the CQI model on quality of care for various services and to identify factors that enabled or impeded quality improvements. We assessed changes in quality of care for seven services over a two-year implementation period and compared these changes against other PBF districts. We also conducted focus group discussions and in-depth interviews with district and facility-level health workers and managers after implementation to explore enabling and impeding factors affecting program performance. Among the seven services assessed, CQI was associated with quality improvement in primary health centers for two: postnatal care and maternal delivery care. Enabling factors included strengthened leadership, teamwork and joint decision-making at facilities; and supportive supervision. Impeding factors included fragmentation of quality assurance policies; staff shortages and turnover; and gaps in the CQI training. Improvements were limited when considering the full breadth of potential outcomes but arise in certain areas of core focus of the CQI program. In order to see large scale improvement in the quality of healthcare in Zimbabwe, CQI should be seen as one potential tool in a broader health systems quality improvement strategy. Highlights: Zimbabwe's Continuous Quality Improvement program created modest quality improvements. CQI was associated with improvements in two of the seven services assessed. Strengthened leadership and supportive supervision enabled some improvement. Fragmented quality policies, staff shortages and training gaps impeded further progress.